„Biblia Paulińska” (2008) wobec tradycji polskich (katolickich) przekładów Pisma świętego - Matuszczyk-Podgórska, Bożena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The aim of the paper is to illustrate translators’ strategies adopted for rendering in Polish the so-called Pauline Bible, the latest (2008) Catholic version of the original Script. This translation is a response to the challenges posed by contemporary culture; it is meant to convey Biblical ideas in language appealing to the cntemporary recipient. At the same time, the translators and editors engaged in this task had to take into account the deeply rooted in the Polish culture traditions of translating the Bible and rendering its message: 1) the tradition of faithful philological translation, 2) the tradition of the Polish Biblical translation style (established by the Rev. Jakub Wujek), 3) the tradition of the Millennium Bible (1965). The author uses selected samples to illustrate how the Pauline Bible, departing from the method of literal translation, manifested in, e.g., reflecting Semitisms, does not abandon the principle of fidelity and remains consitent with the idiosyncrasies of the Polish Biblical style. This is in accordance with the overall intention to reconcile fidelity with comprehensibility. The paper is an introduction to further research into issues involved in the said translation.
Keywords: Philological translation; Biblical Polish; Polish Biblical style